Internationalization strategy and performance of small and medium sized enterprises - Jonas Onkelinx; Leo Sleuwaegen (National Bank of Belgium, 2010)
Focusing on the timing and geographical scope of import and export activities of Belgian small and medium sized enterprises (SMEs), the paper analyzes the importance, structural features and performance implications of firms that recently started to export following the geographical configuration of their international trade operations and their year of establishment. The analysis allows us to separate firms that started to export in the period 1998-2005 into four distinct groups: born internationals, i.e. firms which were established less than five years before their first year of exporting and exporting to less than five countries in the same region (regional focus), born globals; young firms but with a more internationally diversified export portfolio, born again globals, i.e. firms similar to born globals but established longer than five years before their first exports and traditional internationalizers, firms established more than five years before their first export operations characterized by a narrow geographical scope of their exports. We find SME export growth to be driven by a small group of born global firms, accounting for 60 per cent of the total increase in SME exports between 1998 and 2005. Analyzing the structural feature of the different types of firms, we find born globals to be more productive and characterized by a higher R&D spending and intangible asset intensity compared to other types of traders. We next test if the typology matters for the observed export performance differences across firms over time. We find that born globals grow faster in terms of export sales, have a stronger commitment to export markets and are more likely to continue exporting. Born globals also have the highest failure rate, traditional internationalizers the lowest. These findings suggest strong risk/return tradeoffs among the strategies chosen by the different types of firms. Performing a dynamic analysis of changes in trade configurations of firms over the observation period, we investigate how these changes have an impact on performance. Specific attention is paid to firms that stop importing/exporting. Especially firms that move from being exporters to become two-way traders, i.e. also starting to import goods from other countries show the most marked increases in turnover and productivity. The final part of the study analyzes the relationship between export and import activities to particular countries following the sequence in which they occur. We find that the probability to start importing from a country is 4 times higher for firms already exporting to that country than for trading SMEs without prior export experience in that country.
Keywords: 330; Internationaler Markteintritt; KMU; Globalisierung; Belgien